The Influence of Social Media on Structural Changes in Urban Communities - Larisu, Zulfiah (Kamara Journal, 2025)
Social media has become a primary space for urban interaction, influencing not only communication patterns but also changing the city's social and cultural structures. This study aims to critically examine the influence of social media on structural social and cultural changes in urban communities. The research method used is a descriptive qualitative approach through literature studies, in-depth interviews with key informants (community leaders, youth, and activists), and digital observation (netnography) on Instagram, TikTok, Twitter (X), and WhatsApp Group platforms. Data were analyzed using qualitative content analysis and thematic analysis techniques, accompanied by source triangulation to maintain validity. The results show that social media strengthens social cohesion by expanding citizen participation, facilitating the construction of hybrid identities for the younger generation, and changing the meaning of urban space through digital representation. Social media also plays a role as a means of public deliberation in urban governance. However, challenges such as social polarization, cultural homogenization, and inequality in digital representation have been identified, which have the potential to widen social disparities in urban areas. In conclusion, social media has a dual influence: it is both an instrument for revitalizing local culture and a risk to diversity. Therefore, digital literacy policies and inclusive cyberspace management are needed so that social media can function optimally as an instrument for empowering urban communities.